David Richter, Viktorin Kornel ze Všehrd a Chrudim, Chrudim 2020 - Jan Boukal (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis)
Book review on David Richter, Viktorin Kornel ze Všehrd a Chrudim, Tiskárna PORS s.r.o, Chrudim 2020, 64 stran, ISBN: 978-80-86585-36-9